Illuminating Wealth Management: Insights From Maqasid Al-Sharia - Ward, Tyrone Brandon (Tujjar International Journal of Islamic Economics Development, 2023)
This paper explores the role of Maqasid al-Shariah within the framework of Islamic wealth management, shedding light on how it promotes a holistic, ethical, and sustainable approach to financial practices. Maqasid al-Shariah, a guiding principle based on the broader intentions of Islamic law, influences wealth management by infusing ethical considerations and ensuring alignment with societal benefits. Central to this is the five fundamental principles of Maqasid al-Shariah, which strive to promote welfare and justice in both worldly matters and the afterlife. This paper also elucidates the integration of these principles in wealth management practices, such as Islamic mutual funds, microfinance, and Zakat funds, and their influence on policy and governance within Islamic financial institutions. Furthermore, the paper navigates the challenges and opportunities in Islamic wealth management in light of Maqasid al-Shariah, providing strategic recommendations to reinforce Islamic finance practices, harmonize regulatory frameworks, and integrate financial technology effectively. Through the lens of Maqasid al-Shariah, the paper proposes a path forward that balances the financial, ethical, and social dimensions of Islamic wealth management. Keywords: maqasid al-Shariah, Islamic wealth management, fintech in Islamic finance